Intravitreal injection of IGFBP-3 restores normal insulin signaling in diabetic rat retina. - Youde Jiang; Qiuhua Zhang; Jena J Steinle (PLoS ONE)
Diabetes-induced changes in growth factor binding protein 3 (IGFBP-3) and tumor necrosis factor alpha (TNFα) have been linked to decreased insulin receptor signaling in diabetic retinopathy. Our previous studies in retinas of diabetic rats have shown that Compound 49b, a novel β-adrenergic receptor agonist, prevented diabetic changes by increasing IGFBP-3 and decreasing TNFα, thus restoring insulin signaling and protection against diabetic retinopathy. The current study was designed to determine whether boosted expression of IGFBP-3 NB (a non-IGF-1 binding form of IGFBP-3) alone is sufficient to mimic the full actions of Compound 49b in protecting against diabetic retinopathy, as well as testing whether IGFBP-3 NB is linked to a restoration of normal insulin signal transduction. Two months after initiation of streptozotocin-induced diabetes, rats received a single intravitreal injection of IGFBP-3 NB plasmid in the right eye. Four days after injection, electroretinogram (ERG) analyses were performed prior to sacrifice. Whole retinal lysates from control, diabetic, diabetic + control plasmid, and diabetic+ IGFBP-3 NB were analyzed for IGFBP-3, TNFα, suppressor of cytokine signaling 3 (SOCS3), and insulin receptor signaling partners using Western blotting or ELISA. Data show that a single intraocular injection of IGFBP-3 NB in diabetic animals significantly reduced TNFα levels, concomitant with reductions in IRS-1Ser307, SOCS3, and pro-apoptotic markers, while restoring insulin receptor phosphorylation and increasing anti-apoptotic marker levels. These cellular changes were linked to restoration of retinal function. Our findings establish IGFBP-3 as a pivotal regulator of the insulin receptor/TNFα pathway and a potential therapeutic target for diabetic retinopathy.